The structure and dynamics of Luther's Catechism - Zwanepol, K. (Faculty of Theology, University of the Free State, 2011)
This contribution deals with the structure of Luther’s Catechism, one of Protestant basic texts. First an outline is given of the history of the composition of the text. Next some remarks are made on Luther’s purpose in bringing out this Catechism. The more as scholarly discussion about it raised attention is paid to the structure of Luther’s Catechism. Our conclusion is that the five parts of this Catechism are best understood in a circular form which challenges its users to go through the material time and again. Only then its specific dynamics will manifest itself which make Luther’s Catechism very suitable for instruction about the Christian Faith at several levels. Following this impetus this Catechism against a tradition of misuse as a confessional text book might be recaptured as life book which proves to be useful in handing down the relevancy of Protestant tradition in the entire faith community.
Keywords: Luther; Catechism; Structure; Dynamics